Hydroxyaldimines as potent in vitro anticryptococcal agents. (20th May 2013) - Magalhães, T.F.F.; da Silva, C.M.; de Fátima, Â.; da Silva, D.L.; Modolo, L.V.; Martins, C.V.B.; Alves, R.B.; Ruiz, A.L.T.G.; Longato, G.B.; de Carvalho, J.E.; de Resende‐Stoianoff, M.A.
Abstract: Cryptococcosis, a fungal infection that affects both immunocompromised and immunocompetent individuals, contributes to increasing indices of mortality and morbidity. The development of resistance by Cryptococcus spp., the limited number of commercial antifungal drugs and the various side effects of these drugs cause the treatment of cryptococcosis to be a challenge. The in vitro anticryptococcal activity of nine hydroxyaldimines was evaluated against 24 strains of Cryptococcus spp. Antifungal susceptibility was evaluated using a broth microdilution assay following the Clinical and Laboratory Standards Institute guidelines, using fluconazole as a positive control. Parameters such as the minimum inhibitory concentration and the minimum fungicidal concentration (MIC and MFC, respectively) were also determined. Antiproliferative activity on the normal cell line VERO was assessed 48 h post‐compound exposure to determine the selectivity index (SI) of the hydroxyaldimines and fluconazole. All hydroxyaldimines were active against Cryptococcus spp. strains. Compounds 3A9 and 3B7 were the most potent against the Cryptococcus gattii and Cryptococcus neoformans strains. Selectivity indices also revealed that 3B10, 3C3, 3D3 and 3D9 are good candidates for in vivo studies. The in vitro anticryptococcal activity of hydroxyaldimines against various strains of C. gattii and C. neoformans indicates the potential of this class of molecules as lead compound for the development of selective and efficient anticryptococcal agents. Significance and Impact of the Study: The effectiveness of hydroxyaldimines for inhibition of Cryptococcus spp. growth and their low toxicity against healthy monkey kidney epithelial cells makes them promising lead compounds for the design of new anticryptococcal agents. Abstract : Significance and Impact of the Study: The effectiveness of hydroxyaldimines for inhibition of Cryptococcus spp. growth and their low toxicity against healthy monkey kidney epithelial cells makes them promising lead compounds for the design of new anticryptococcal agents.